Climate Forecast and Decision Making in Agriculture - Clyde Fraisse; David Zierden; Norman Breuer; John Jackson, Jr.; Charles Brown (EDIS)
Farmers make decisions on a daily basis that affect their financial returns and overall welfare. The consequences of decisions are often not known with certainty until long after the decisions occur and the outcomes can be better or worse than expected. Often the decisions are made based on some type of forecast, such as price, weather, or climate. This document is ABE 352, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Sciences, University of Florida. Published July 2004.